Tapering of biological treatment in autoinflammatory diseases: a scoping review - Tatjana Welzel; Lea Oefelein; Marinka Twilt; Marc Pfister; Jasmin B. Kuemmerle-Deschner; Susanne M. Benseler (BMC, 2022)
Abstract Background Biological treatment and treat-to-target approaches guide the achievement of inactive disease and clinical remission in Autoinflammatory Diseases (AID). However, there is limited evidence addressing optimal tapering strategies and/or discontinuation of biological treatment in AID. This study evaluates available evidence of tapering biological treatment and explores key factors for successful tapering. Methods A systematic literature search was conducted in Embase, MEDLINE, Cochrane Database of Systematic Reviews and Cochrane Central Register of Controlled Trials using the OVID platform (1990-08/2020). Bibliographic search of relevant reviews was also performed. Studies/case series (n ≥ 5) in AID patients aged ≤ 18 years with biological treatment providing information on tapering/treatment discontinuation were included. After quality assessment aggregated data were extracted and synthesized. Tapering strategies were explored. Results A total of 6035 records were identified. Four papers were deemed high quality, all focused on systemic juvenile idiopathic arthritis (sJIA) (1 open-label randomized trial, 2 prospective, 1 retrospective observational study). Biological treatment included anakinra (n = 2), canakinumab (n = 1) and tocilizumab (n = 1). Strategies in anakinra tapering included alternate-day regimen. Canakinumab tapering was performed randomized for dose reduction or interval prolongation, whereas tocilizumab was tapered by interval prolongation. Key factors identified included early start of biological treatment and sustained inactive disease. Conclusion Tapering of biological treatment after sustained inactive disease should be considered. Guidance for optimal strategies is limited. Future studies may leverage therapeutic drug monitoring in combination with pharmacometric modelling to further enhance personalized "taper-to-target" strategies respecting individual patients and diseases aspects.